The EU Integration Process of the Western Balkans in the Aftermath of 2015’s Refugee Crisis - Julija Brsakoska Bazerkoska (My University, 2022)
The worst contemporary refugee crisis that occurred during the summer of 2015 challenged the basic values of the European Union. There had never been a time when the need for a consistent approach, both from the individual Member States and the EU as a whole, was more urgent. The Union’s response during 2015’s refugee crisis was unreliable, fragmented, and it largely affected the Western Balkan countries that are now aspiring to become EU Member States. This paper analyses how the EU’s response to the refugee crisis has affected and still affects the countries in the Western Balkans, which are all in different stages of their European integration. The refugee crisis created many challenges for the Western Balkan countries which are all weak democracies, and which have unstable institutions. This paper also analyses the numerous domestic costs connected to these countries when faced with the refugee crisis. Finally, the paper argues that, although largely harmonized with the EU acquis, the legislative and institutional frameworks for migration management in Western Balkan countries need further adjustment.
Keywords: Western Balkans; Refugee crisis; EU enlargement.